A mulher negra no ponto cego das políticas públicas de gênero e de raça: análise crítica da representatividade da mulher negra no Congresso Nacional - Antunes, Cássia de Jesus (2025)
Black women are among the most underrepresented social groups in the National Congress, in terms of gender and race. Party barriers, racism, sexism, and social, gender, race, or intersectional inequalities seem to work together to limit the fair and equitable political representation of certain population groups. In this context, this work, developed empirically, within the scope of the professional master's degree, line of research Regulation, Effectiveness and Constitutional Control of Public Policies, aimed to identify whether black women are in the blind spot of public policies to promote the political participation of women and black people and what symbolic and institutional mechanisms maintain the low representation of black women in the National Congress. Therefore, it used two data collection techniques: documentary research, especially with regard to data related to political representation in the National Congress in the last two federal elections, 2018 and 2022; and semi-structured interviews with black women candidates elected and not elected to federal legislative positions and black women leaders of feminist and anti-racist social movements. The analysis of qualitative content was performed using Bardin (2016) content analysis technique, with the help of Atlas.ti software. As a result, political parties were identified in the interviews as operationalizing obstacles to black women's access to elected political positions, revealing exclusionary party structures and exclusionary dynamics. Regarding the difficulties faced by black women in political campaigns, the lack of resources and lack of confidence in the ability of black women were raised as the greatest challenges. To construct the practical-theoretical framework of the underrepresentation of black women in the National Congress, we sought to organize the challenges and factors correlated to the problem into two groups, symbolic mechanisms and institutional mechanisms, in order to highlight the dual aspect of underrepresentation. This study confirms that black women remain marginalized in institutional politics and broadens the understanding of the problem by using intersectionality as an analytical tool. By relating the underrepresentation of these women to that of other marginalized groups and suggesting paths for change, the research fulfills a dual role: rigorously diagnosing representational distortions and encouraging reflection and action to overcome these challenges.